2021
DOI: 10.2500/aap.2021.42.210017
|View full text |Cite
|
Sign up to set email alerts
|

Physician and patient perspectives on the management of hereditary angioedema: a survey on treatment burden and needs

Abstract: Hereditary angioedema (HAE) is a rare disorder caused by genetic mutations that lead to recurrent episodes of swelling in various parts of the body. Prophylactic treatment is common for patients with HAE, and the therapeutic options have expanded in recent years. The current standard of care for prophylactic HAE therapies is subcutaneous treatment, which can be self-administered at home, greatly improving patient quality of life. As new therapies emerge, it is important for patients and physicians to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Prophylactic therapeutic options have grown in the past two decades to include lanadelumab (Takhzyro), SC C1-INH (Haegarda), and IV C1-INH (Cinryze). All these treatment options are either large biologics or peptides that must be administered via injection or infusion leading to a significant treatment burden; therefore, the development of an oral long-term prophylactic therapy could increase convenience and improve the ease of administration, reducing treatment burden and improving the quality of life (QoL) in patients with HAE . No oral drugs have been approved for the prevention or treatment of HAE, though a few small molecule PKal inhibitors have been reported. We report the discovery of Berotralstat (BCX7353), an orally bioavailable small molecule PKal inhibitor that has been effective in preventing HAE attacks and has recently been approved by the U.S. Food and Drug Administration (FDA), Japan’s Ministry of Health, Labor, and Welfare (MHLW), and the European Commission for the prophylactic treatment of HAE in patients 12 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic therapeutic options have grown in the past two decades to include lanadelumab (Takhzyro), SC C1-INH (Haegarda), and IV C1-INH (Cinryze). All these treatment options are either large biologics or peptides that must be administered via injection or infusion leading to a significant treatment burden; therefore, the development of an oral long-term prophylactic therapy could increase convenience and improve the ease of administration, reducing treatment burden and improving the quality of life (QoL) in patients with HAE . No oral drugs have been approved for the prevention or treatment of HAE, though a few small molecule PKal inhibitors have been reported. We report the discovery of Berotralstat (BCX7353), an orally bioavailable small molecule PKal inhibitor that has been effective in preventing HAE attacks and has recently been approved by the U.S. Food and Drug Administration (FDA), Japan’s Ministry of Health, Labor, and Welfare (MHLW), and the European Commission for the prophylactic treatment of HAE in patients 12 years and older.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the studies from United States reported established use of first‐line HAE treatment options, with the use of C1‐INH reported in up to 60.7% of patients and the use of lanadelumab (since 2018) reported in up to 53.3% of patients in separate studies 37–42 . Widespread use of C1‐INH was also reported in Canada (93.5% of physicians reported prescribing C1‐INH for LTP), 64 Germany (ongoing LTP and/or STP with C1‐INH reported in up to 65.0% of patients), 65 and Puerto Rico (LTP with C1‐INH reported in up to 68.7% patients who were taking prophylaxis) 66 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the adoption of first‐line LTP options, the frequent use of second‐line LTP therapies persisted even in these countries, with 27.2% of patients from the United States reporting the use of androgens for LTP 39 and 40.0% of patients from Germany reporting the use of androgens for LTP and/or STP 65 . In a survey of physicians from Canada, 41.9% of physicians reported prescribing androgens and 19.4% reported prescribing antifibrinolytics 64 ; in two similar surveys of physicians from the United States, up to 38% of physicians reported currently prescribing androgens and up to 11% of physicians reported currently prescribing antifibrinolytics 37,38 . These trends are similar to the findings of multinational (Australia, Austria, Canada, France, Germany, Spain, Switzerland, and United Kingdom) study from 2018 which reported that 45.7% of patients overall received LTP with C1‐INH, 34.4% with androgens, and 17.9% with tranexamic acid 62 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations